2010
DOI: 10.1007/s10681-010-0240-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of adult plant stripe rust resistance in wheat and identification of pyramided QTL genotypes

Abstract: The Puccinia striiformis f. sp. tritici (Pst) pathotype, 134 E16A?, detected in 2002 in Australia, produced relatively lower and higher adult plant stripe rust responses, respectively, on cultivars Kukri and Janz in comparison to the pre-2002 Pst pathotype 110 E143A?. Molecular mapping of adult plant stripe rust response variation among 180 Kukri/Janz-derived doubled haploid lines over 4 years, two each with Pst pathotypes 110 E143A? and 134 E16A?, was performed. QYr.sun-7B and QYr.sun-7D were consistently con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 36 publications
3
56
0
1
Order By: Relevance
“…In the study of Boukhatem et al (2002), QYR2 accounted for only 15.4% of the phenotypic variation. Bariana et al (2010) identified an APR QTL proximal to the region defining QYr. Hao et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Boukhatem et al (2002), QYR2 accounted for only 15.4% of the phenotypic variation. Bariana et al (2010) identified an APR QTL proximal to the region defining QYr. Hao et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Oligoculm (Suenaga et al 2003), the Australian cv. Janz (Bariana et al 2010) and the French cv. Flinor (Feng et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This had been identified in numerous studies and is described as group 3 on 1BL (QRYr1B.3) in Table 1 (Bariana et al 2001, 2010; Jagger et al 2011; Lillemo et al 2008; Melichar et al 2008; Rosewarne et al 2008, 2012; William et al 2006; Zwart et al 2010). There is a wide range in the LOD (2.8–23) and PEV (4.5–65) scores indicating the variability that this locus can contribute.…”
Section: Groupmentioning
confidence: 96%
“…However, Yr29 is important as is demonstrated by the number of significant environments tested. Nearly every study finds this locus significant in every environment tested with the exception of Bariana et al (2010). Interestingly, Bariana et al (2010) also had Lr34/Yr18 (hereafter termed Yr18 ) segregating in that population and it is now becoming apparent that when those two loci are in the same genetic background, the Yr29 locus has lesser effect (Lillemo et al 2008; Suenaga et al 2003; Yang et al 2013).…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation